Dewi Ayu’s Electra Complex as seen in Eka Kurniawan’s Beauty Is A Wound - Handoko, Putut; Kartika, Dwi Indah (Dinamika : Jurnal Sastra dan Budaya, 2016)
This study aims to analyze Dewi Ayu’s Electra Complex as Seen in Eka Kurniawan’s Beauty Is A Wound. The objectives of the study are: (1) to find out the proofs of Dewi Ayu’s Electra Complex as Seen in Eka Kurniawan’s Beauty Is A Wound; (2) to find out the causal factors of Dewi Ayu’s Electra Complex as Seen in Eka Kurniawan’s Beauty Is A Wound; and (3) to find out the effects of Dewi Ayu’s Electra Complex on herself and on Ma Gedik as Seen in Eka Kurniawan’s Beauty Is A Wound.  The theory used by the thesis writer is the theory of Electra Complex by Freudian theories in psychoanalysis approach and she also applies a qualitative research. Keywords: Psychoanalysis, Electra complex, Defence Mechanism.